Phase identification of vanadium oxide thin films prepared by atomic layer deposition using X-ray absorption spectroscopy. Issue 44 (15th July 2020) - Kim, Yejin; Song, Gwang Yeom; Nandi, Raju; Cho, Jae Yu; Heo, Jaeyeong; Cho, Deok-Yong
Abstract : X-ray absorption spectroscopy reveals the local structures of atomic-layer-deposited vanadium oxide films subject to heat treatments. Abstract : The chemical and local structures of vanadium oxide (VO x ) thin films prepared by atomic layer deposition (ALD) were investigated by soft X-ray absorption spectroscopy. It is shown that the as-deposited film was a mixture of VO2 and V2 O5 in disordered form, while the chemistry changed significantly after heat treatment, subject to the different gas environment. Forming gas (95% N2 + 5% H2 ) annealing resulted in a VO2 composition, consisting mostly of the VO2 (B) phase with small amount of the VO2 (M) phase, whereas O2 annealing resulted in the V2 O5 phase. An X-ray circular magnetic dichroism study further revealed the absence of ferromagnetic ordering, confirming the absence of oxygen vacancies despite the reduction of V ions in VO2 (V 4+ ) with respect to the precursor used in the ALD (V 5+ ). This implies that the prevalence of VO2 in the ALD films cannot be attributed to a simple oxygen-deficiency-related reduction scheme but should be explained by the metastability of the local VO2 structures.